EFFECTS OF ANTI ANXIETY DRUG MIDAZOLAM AS PRETREATMENT THERAPY FOR ANXIETY OF ZEBRA FISHES INDUCED BY THE EXPOSURE OF UNFAMILIAR ENVIRONMENT OF AQUATIC WHITE/BLACK MAZE - Vada, Surendra; Goli, Divakar; Bose, Anirbandeep; Sharma, Uday Raj (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectves: The objective of our present research investigation was to evaluate the effectiveness of the aquatic white/black plus maze model to evaluate the efficacy of different treatment drugs on zebra fish behavior studies. Methods: Animals were divided into three groups each containing six animals. The first two groups were pretreated with lower and higher doses of midazolam and then they were exposed to unfamiliar environments of aquatic white/black plus maze. The last group of animals was only immersed into the unknown familiar in the form of aquatic white/black plus maze without any pretreatment of the drugs. Results: The results illustrated that the pretreatment drugs certainly improved the behavior status of the animal in the form of releasing anxiety and stress, but the doses of different pretreatment have no significant effects on improvement of behavioral status. Conclusion: In conclusion, it can be described that this model is highly effective to find the proper drug for the treatment of anxiety but it is not so effective to find the proper dose of treatment. Keywords: Midazolam, Zebra fish, White/black maze, Anti anxiety, Pretreatment therapy.